2020
DOI: 10.1021/acsami.0c02034
|View full text |Cite
|
Sign up to set email alerts
|

Combating Pseudomonas aeruginosa Biofilms by a Chitosan-PEG-Peptide Conjugate via Changes in Assembled Structure

Abstract: Pseudomonas aeruginosa (P. aeruginosa) biofilms are associated with a wide range of infections, from chronic tissue diseases to implanted medical devices. In a biofilm, the extracellular polymeric substance (EPS) causes an inhibited penetration of antibacterial agents, leading to a 100− 1000 times tolerance of the bacteria. In view of the water-filled channels in biofilms and the highly negative charge of EPS, we design a chitosan-polyethylene glycol-peptide conjugate (CS-PEG-LK 13 ) in this study. The CS-PEG-… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
53
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
5
2
1

Relationship

1
7

Authors

Journals

citations
Cited by 45 publications
(55 citation statements)
references
References 35 publications
2
53
0
Order By: Relevance
“…Experiments with stealth, poly(ethylene glycol) coated liposomes and polystyrene nanoparticles (see Figure 3), unable to adsorb to biofilm components, demonstrated that liposomes with diameters above 100-130 nm were unable to diffuse through channels in Burkholderia multivorans and P. aeruginosa biofilms (see Figure 3) (Forier et al 2014). A similar minimal width of 100 nm was reported in order to avoid adsorption of antimicrobials to channel walls upon diffusion-controlled penetration of an antimicrobial in an infectious biofilm (Ju et al 2020). However, intra-colony channels with much larger diameters of around 10 mm have also been described in E. coli, using giant objective lens microscopy with a high numerical aperture at low magnification ("mesoscopy") (Rooney et al 2020) and even wider channels (18-99 mm) have been described in P. aeruginosa (Lei et al 2020).…”
Section: Structure Of Water-filled Regions In Biofilms: Channels and Poresmentioning
confidence: 72%
“…Experiments with stealth, poly(ethylene glycol) coated liposomes and polystyrene nanoparticles (see Figure 3), unable to adsorb to biofilm components, demonstrated that liposomes with diameters above 100-130 nm were unable to diffuse through channels in Burkholderia multivorans and P. aeruginosa biofilms (see Figure 3) (Forier et al 2014). A similar minimal width of 100 nm was reported in order to avoid adsorption of antimicrobials to channel walls upon diffusion-controlled penetration of an antimicrobial in an infectious biofilm (Ju et al 2020). However, intra-colony channels with much larger diameters of around 10 mm have also been described in E. coli, using giant objective lens microscopy with a high numerical aperture at low magnification ("mesoscopy") (Rooney et al 2020) and even wider channels (18-99 mm) have been described in P. aeruginosa (Lei et al 2020).…”
Section: Structure Of Water-filled Regions In Biofilms: Channels and Poresmentioning
confidence: 72%
“…ANS fluorescence and PI fluorescence measurements of the hydrogel-treated groups show obvious enhancements compared with the control group (Figure S24, Supporting Information), indicating that bacteria died and their membranes turned over after treatment. [58] On the basis of these observations, we inferred that the antibacterial activity of the FLN-based hydrogel, like that of other amyloid fibrils, is based on a membrane-disrupting mechanism (Figure 7h). Interestingly, the FLN nanofibrils could capture the planktonic microorganisms and achieved bead-like bacterial agglomeration (MRSA and P. aeruginosa), as recorded by AFM (Figure 7g), which is likely a consequence of the organized β-sheet structure of the nanofibrils and the positive charge of the Lys exposed on the surface of the nanofibrils (Figure 3).…”
Section: Antibacterial Mechanism Of the Fln-based Hydrogelmentioning
confidence: 86%
“…Notably, bacteria do not easily develop resistance to such a physical-damage-based antibacterial mechanism. [58] A diabetic ulcer, as a typical chronic wound, is prone to wound nonclosure and persistent microbial infection, eventually resulting in a 41% possibility of amputation. Diabetic ulcers thus pose a large challenge to medicine and represent a financial burden to society.…”
Section: Antibacterial Mechanism Of the Fln-based Hydrogelmentioning
confidence: 99%
“…However, recent evidence revealed that chitosan penetrates the cell membrane of P. aeruginosa, releasing the cell contents and aggregating the residue cytoplasmic material into a mass. It was presumed that the cytoplasmic material was agglomerated by flocculation of chitosan after entering the cell [50], an effect that would overcome the resistance mechanisms mentioned above. Finally, so far, this finding could mean highly deacetylated chitosan is a potential antimicrobial agent to use against CST-resistant MDR strains.…”
Section: Antimicrobial Activitymentioning
confidence: 99%